ANALISIS PENINGKATAN USAHA MIKRO KREATIF DESA BEJIJONG MELALUI PESONA WISATA BUDAYA - Amelia; M. Kendry Widianto; Hasan Ismail (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2025)
This study aims to analyze cultural-based tourism development strategies as an effort to enhance creative micro-enterprises in Bejijong Village, Trowulan District, Mojokerto Regency. The village possesses rich cultural and historical heritage from the Majapahit Kingdom, which serves as the main attraction for cultural tourism, including sites such as Brahu Temple, Siti Inggil Hermitage, and the Sleeping Buddha Statue. This research employs a qualitative approach using observation, in-depth interviews, and documentation techniques, with data analyzed through the SWOT method. The results indicate that cultural tourism development has a significant impact on local economic growth through the formation of a culture-based MSME ecosystem. Development strategies that are rooted in local potential and cultural wisdom values encourage active community participation in environmental preservation, social empowerment, and income improvement. The SWOT analysis places Bejijong Village in an aggressive strategy position, meaning it can maximize internal strengths and external opportunities to promote sustainable growth. These findings highlight the importance of integrating cultural preservation with the strengthening of the local economy in the development of cultural tourism villages.